Evaluation of the Ozone Effects on Human Hair Fiber: A Preliminary In Vitro Study - Laurindo Igreja Marrafa, Pedro Augusto; Kawata, Bianca Akemi; Braga Carneiro, Hulair [UNESP]; de Souza Botelho, Túlia; Carvalho, Henrique Cunha; de Castro Lima, Cibele Rosana Ribeiro; Passador, Fabio Roberto; Barros Mello, Carina; Uchoa Fernandes, Adjaci; Fernandes, Adriana Barrinha; de Lima, Carlos José (Taylor & Francis, 2024)
Research with ozone has shown potential for applicability, including use of ozone as an environmentally friendly alternative to personal care products (PCPs). However, for hair, there are few studies indicating the safety of using ozone gas, especially when in contact with hair fiber. The aim of this study was to characterize possible physicochemical changes that may occur in hair strands exposed to ozone gas. Scanning electron microscopy (SEM) and profilometry for surface analysis, Fourier transform infrared spectroscopy (FTIR) with attenuated total reflection (ATR) for chemical analysis, Thermogravimetry, and grazing incidence X-ray diffraction (GIXRD) for structural analysis were used. SEM and profilometry techniques showed evidence of changes in appearance of the hair fiber. While FTIR-ATR showed degradation of characteristic peaks on the hair infrared spectrum, with major changes at peaks 2920, 2851, 1633, 1235, 1075, and 1043 cm−1, also associated with the cuticle and mainly related to the cell membrane complex (CMC). Thermogravimetry and GIXRD have shown the possible effect of ozone on human hair amino acids. The results obtained indicated that ozone gas applied on human hair showed oxidative action. Therefore, additional studies are required before discussing the replacement of PCPs by gas ozone.
Keywords: Amino acids; Human hair; Oxidation; Ozone; Personal care products (PCPs)